The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.1049/mna2.12086
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic microswimmers with infrared‐induced shape transformation

Abstract: Soft untethered microswimmers have recently been demonstrated to be capable of transporting and delivering cargos by external control while maintaining biocompatibility and safety. However, such microswimmers still suffer from complex and inconvenient fabrication processes and control methods, which impedes their clinical translation. In this paper, an easy-to-fabricate, magnetic-driven and IR-induced shape transformative microswimmer is presented. This microswimmer can be fabricated in a fast, low-cost and hi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 60 publications
0
1
0
Order By: Relevance
“…In addition to solving the problem of exploration of biodegradable materials, it is necessary to consider whether or not the rate of degradation and degradable products are good in biocompatibility. Yang et al [141] recently reported a magnetic microswimmer with biocompatible and biodegradable components. On the other hand, because of the advantages of insensitivity to biological tissues, precision control and positioning, magnetic fields have become the preferred driving source for biodegradable micro-nano robots.…”
Section: Minimum Invasion [96]mentioning
confidence: 99%
“…In addition to solving the problem of exploration of biodegradable materials, it is necessary to consider whether or not the rate of degradation and degradable products are good in biocompatibility. Yang et al [141] recently reported a magnetic microswimmer with biocompatible and biodegradable components. On the other hand, because of the advantages of insensitivity to biological tissues, precision control and positioning, magnetic fields have become the preferred driving source for biodegradable micro-nano robots.…”
Section: Minimum Invasion [96]mentioning
confidence: 99%